Boosting growth to end hunger by 2025: The role of social protection - Wouterse, Fleur Stephanie; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2018)
Social protection programs—public or private initiatives that aid the poor and protect the vulnerable against livelihood risks—can effectively be used to assist those trapped, or at the risk of being trapped, in chronic poverty. These programs aim to address chronic poverty through redistribution and protect vulnerable households from falling below the poverty line. Although investments in social protection programs are often motivated by equity concerns, they can also contribute to economic growth by, for example, encouraging savings, creating community assets, and addressing market imperfections. Despite their potential and proliferation, not enough is known about social protection programs in Africa. The 2017–2018 Annual Trends and Outlook Report (ATOR) reduces this knowledge gap by focusing on the potential of such programs on the continent and the corresponding opportunities and challenges. The chapters of the Report highlight the benefits of these programs, not only to their direct recipients but also others in the community through spillover effects. They also underscore the importance of appropriate design and sustainability to fully realize the potential of social protection programs.